California County Planning Commissioners Conference at Fresno Airport Holiday Inn - Watkins, Howard::::::::: (1982)
Don Williams (Madera), Marjorie Shields (Tulare), State Senator Rose Ann Vuich, Jack Lish (Placer) and wife